A silicone composition for human bionic skin and a preparation method thereof
Patent Information
- Application Number
- CN202611221480.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-12
- Publication Date
- 2026-10-13
AI Technical Summary
[0005]本发明的目的在于提出一种人体仿生皮肤用有机硅组合物及其制备方法,以解决上述硅橡胶的柔软触感与材料强度之间的矛盾,以及引入生物活性填料后材料仿真触感下降的问题
所述有机硅组合物应用于人体仿生皮肤,引入了TPU微珠、硅树脂和季铵表面处理羟磷灰石,改善人体仿生皮肤的手感,并增强了回弹性。季铵表面处理羟磷灰石兼具抗菌性、回弹性和表面爽滑三重功能。季铵表面处理羟磷灰石作为生物活性无机填料引入有机硅体系,具有抗菌效果,还能在基体中形成物理交联点,提升材料的撕裂强度和拉伸强度;同时,羟磷灰石表面的羟基与有机硅分子链形成氢键作用,改善了材料表面爽滑感,减少了硅橡胶固有的生涩触感。此外,季铵表面处理羟磷灰石与有机硅基体具有良好的界面相容性,有利于均匀分散,避免因团聚导致的局部应力集中。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of silicone rubber, and more particularly to a silicone composition for human biomimetic skin and its preparation method. Background Technology
[0002] With its low surface energy, excellent biocompatibility, aging resistance, adjustable hardness and softness, and easy molding properties, silicone rubber has become the mainstream matrix material in the field of biomimetic skin and is widely used in artificial skin, soft robots, wearable devices, soft toys and prosthetic skin.
[0003] In existing technologies, to achieve a soft touch similar to real human skin, the hardness of silicone rubber needs to be reduced. However, after the material's hardness is reduced, its tear strength, tensile strength, and abrasion resistance decrease significantly, making it prone to damage during repeated bending and contact friction, which fails to meet the mechanical reliability requirements for long-term use of biomimetic skin. On the other hand, if the amount of filler is increased to enhance mechanical properties, the viscoelasticity of the silicone rubber decreases, resulting in a stiff and rough feel, poor skin-friendliness, and a loss of the soft and smooth touch that biomimetic skin should have.
[0004] Moreover, existing technologies have introduced bioactive fillers such as hydroxyapatite to improve biocompatibility. However, due to insufficient surface modification, these bioactive fillers may exhibit uneven dispersion and weak interfacial bonding in the silicone rubber matrix, resulting in a decrease in the simulated tactile feel of the material. Summary of the Invention
[0005] The purpose of this invention is to provide an organosilicon composition for human biomimetic skin and its preparation method, so as to solve the contradiction between the soft touch and material strength of the above-mentioned silicone rubber, as well as the problem of the decrease in the simulated touch of the material after the introduction of bioactive fillers.
[0006] To achieve this objective, the present invention adopts the following technical solution: This invention provides an organosilicon composition for human biomimetic skin, comprising component A and component B; Component A, by mass fraction, comprises the following components: 1-10 parts quaternary ammonium surface-treated hydroxyapatite, 1-5 parts silica, 1-5 parts nano-alumina, 1-3 parts TPU microspheres, 1-5 parts silicone resin, 1-2 parts powder treatment agent, 10-80 parts low molecular weight vinyl organopolysiloxane, 1-10 parts low molecular weight methyl polysiloxane, 0.1-2 parts low molecular weight polyether modified polyorganosiloxane, 0.01-1 part hydrosilylation catalyst, and 0.01-1 part Component A additive; Component B, by mass fraction, comprises the following components: 1-10 parts quaternary ammonium surface-treated hydroxyapatite, 1-8 parts silica, 1-3 parts nano-alumina, 1-3 parts TPU microspheres, 1-5 parts silicone resin, 1-2 parts powder treatment agent, 10-80 parts low molecular weight vinyl organopolysiloxane, 1-10 parts low molecular weight methyl polysiloxane, 0.1-2 parts low molecular weight polyether modified polyorganosiloxane, 1-8 parts hydrosilylation crosslinking agent, and 0.01-1 parts component B additive; The viscosity of the low molecular weight vinyl organopolysiloxane in components A and B is 1500–2500 CS (25°C), and the molecular weight dispersion is ≤1.3; the viscosity of the low molecular weight methyl polysiloxane in components A and B is 9000–11000 CS (25°C), and the molecular weight dispersion is ≤1.3; the viscosity of the low molecular weight polyether modified polyorganosiloxane in components A and B is 4000–7000 CS (25°C).
[0007] In the aforementioned biomimetic skin silicone composition, the quaternary ammonium surface-treated hydroxyapatite is obtained by modifying hydroxyapatite with quaternary ammonium alkoxysilane or quaternary ammonium alkoxypolysiloxane.
[0008] In the aforementioned biomimetic skin silicone composition, the hydrogen content of the hydrosilylation crosslinking agent is 0.8-1.6%, the Pinwell viscosity is 10-30 cs, and the molecular weight dispersion is ≤1.1.
[0009] In the aforementioned biomimetic skin silicone composition, the low molecular weight vinyl organopolysiloxane includes at least two of the following: vinyl-terminated dimethyl polysiloxane, vinyl-terminated methyl vinyl polysiloxane, methyl vinyl dimethyl polysiloxane, phenyl vinyl polysiloxane, dimethyl vinyl-terminated polydimethylsiloxane, and dimethyl vinyl-terminated polydimethyl methyl vinyl siloxane.
[0010] In the aforementioned biomimetic skin silicone composition, the silica in components A and B is fumed silica, and the specific surface area of the silica is 200–240 m² / g. 2 / g; The nano-alumina particles in components A and B have a particle size of 80–150 nm. The TPU microspheres in components A and B have a particle size of 0.8–1.2 μm; The silicone resin in components A and B is MQ silicone resin, and the groups attached to the silicon atoms of the silicone resin are one or more of methyl, phenyl and vinyl groups, and the number average molecular weight of the silicone resin is 4000 to 5000.
[0011] In the aforementioned biomimetic skin silicone composition, the powder treatment agents in components A and B include one or more of hydroxyl-terminated polydimethylsiloxane, vinyl hydroxyl-terminated polydimethylsiloxane, dimethyldimethoxysilane, dimethyldiethoxysilane, methyltrimethoxysilane, vinyltriethoxysilane, glycidylpropyltrimethoxysilane, and methacrylate-propyltrimethoxysilane.
[0012] In the aforementioned biomimetic skin silicone composition, component A auxiliary agent includes a structure control agent and a color paste, and component B auxiliary agent includes an inhibitor and a color paste; the structure control agent includes one or more of alkylsilanol, oligomeric hydroxyl-terminated polydimethylsiloxane, hydroxyl-terminated polymethylvinylsiloxane, and trimethylsilanol; The inhibitors include one or more of 3-hydroxybutyne, 3-methyl-1-dodecyn-3-ol, 1-ethynyl-1-cyclohexanol, 2-methyl-3-butynyl-2-ol, 3-methyl-1-ethynyl-3-ol, or 3,5-dimethyl-1-hexynyl-3-ol.
[0013] In the aforementioned organosilicon composition for biomimetic human skin, the hydrosilylation catalyst is a platinum complex catalyst, and the platinum content of the hydrosilylation catalyst is 4500–5500 ppm.
[0014] This invention also provides a method for preparing an organosilicon composition for human biomimetic skin, comprising the following steps: Preparation of quaternary ammonium surface-treated hydroxyapatite: Hydroxyapatite was modified to obtain quaternary ammonium surface-treated hydroxyapatite; Preparation of matrix adhesive: Silica, nano-alumina, TPU microspheres and powder treatment agent are kneaded for 1.5 to 2.5 hours to obtain premixed powder; Quaternary ammonium surface-treated hydroxyapatite, low molecular weight vinyl organopolysiloxane, low molecular weight methyl polysiloxane, low molecular weight polyether modified polyorganosiloxane, and silicone resin are added to the premixed powder. After stirring and kneading evenly, the mixture is heated to 110-130℃ and kneaded for 1-2 hours; then heated to 140-150℃ and kneaded for 2.5-3.5 hours; subsequently, it is cooled and stirred for 0.5-1 hour to obtain the matrix adhesive. Preparation of component A: Add hydrosilylation catalyst, component A auxiliary agent and another part of low molecular weight vinyl organopolysiloxane to the matrix gel to obtain component A; Preparation of component B: Add the hydrosilylation crosslinking agent and component B auxiliary agent to the matrix adhesive to obtain component B.
[0015] In the preparation method of the organosilicon composition for biomimetic human skin, the step of preparing quaternary ammonium surface-treated hydroxyapatite includes: adding a quaternary ammonium surface-treatment agent dropwise to hydroxyapatite, adding a surface-treatment catalyst, and kneading at 50-70°C for 2-4 hours to obtain quaternized grafted surface-treated modified hydroxyapatite; the quaternary ammonium surface-treatment agent includes quaternary ammonium alkoxysilane or quaternary ammonium alkoxy polysiloxane. One technical solution of this invention can have the following beneficial effects: The organosilicon composition, applied to biomimetic skin, incorporates TPU microspheres, silicone resin, and quaternary ammonium-treated hydroxyapatite to improve the feel and enhance resilience of the biomimetic skin. Quaternary ammonium-treated hydroxyapatite possesses a triple function of antibacterial properties, resilience, and surface smoothness. As a bioactive inorganic filler introduced into the organosilicon system, quaternary ammonium-treated hydroxyapatite exhibits antibacterial effects and can form physical cross-linking points in the matrix, improving the tear and tensile strength of the material. Simultaneously, the hydroxyl groups on the hydroxyapatite surface form hydrogen bonds with the organosilicon molecular chains, improving the surface smoothness and reducing the inherent roughness of silicone rubber. Furthermore, the quaternary ammonium-treated hydroxyapatite exhibits good interfacial compatibility with the organosilicon matrix, facilitating uniform dispersion and preventing localized stress concentration caused by agglomeration. Detailed Implementation
[0016] The technical solution of the present invention will be further illustrated below through specific embodiments. To facilitate understanding of the present invention, a more comprehensive description is provided below. The present invention can be implemented in many different forms and is not limited to the embodiments described herein. Rather, these embodiments are provided to provide a more thorough and complete understanding of the disclosure of the present invention.
[0017] Where specific techniques or conditions are not specified in the examples, they shall be performed in accordance with the techniques or conditions described in the literature in this field or in accordance with the product instructions. Reagents or instruments whose manufacturers are not specified are all commercially available conventional products.
[0018] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the specification of this invention is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.
[0019] This invention provides an organosilicon composition for human biomimetic skin, comprising component A and component B; Component A, by mass fraction, comprises the following components: 1-10 parts quaternary ammonium surface-treated hydroxyapatite, 1-5 parts silica, 1-5 parts nano-alumina, 1-3 parts TPU microspheres, 1-5 parts silicone resin, 1-2 parts powder treatment agent, 10-80 parts low molecular weight vinyl organopolysiloxane, 1-10 parts low molecular weight methyl polysiloxane, 0.1-2 parts low molecular weight polyether modified polyorganosiloxane, 0.01-1 part hydrosilylation catalyst, and 0.01-1 part Component A additive; Component B, by mass fraction, comprises the following components: 1-10 parts quaternary ammonium surface-treated hydroxyapatite, 1-8 parts silica, 1-3 parts nano-alumina, 1-3 parts TPU microspheres, 1-5 parts silicone resin, 1-2 parts powder treatment agent, 10-80 parts low molecular weight vinyl organopolysiloxane, 1-10 parts low molecular weight methyl polysiloxane, 0.1-2 parts low molecular weight polyether modified polyorganosiloxane, 1-8 parts hydrosilylation crosslinking agent, and 0.01-1 parts component B additive; The viscosity of the low molecular weight vinyl organopolysiloxane in components A and B is 1500–2500 CS (25°C), and the molecular weight dispersion is ≤1.3; the viscosity of the low molecular weight methyl polysiloxane in components A and B is 9000–11000 CS (25°C), and the molecular weight dispersion is ≤1.3; the viscosity of the low molecular weight polyether modified polyorganosiloxane in components A and B is 4000–7000 CS (25°C).
[0020] The organosilicon composition, used in biomimetic human skin, includes component A and component B. Component A contains a hydrosilylation catalyst, and component B contains a hydrosilylation crosslinking agent. They need to be stored separately before use and mixed evenly before curing to ensure that no slow reaction occurs before use, which could cause quality changes.
[0021] Quaternary ammonium-treated hydroxyapatite possesses a triple function: antibacterial properties, resilience, and a smooth surface. Introduced as a bioactive inorganic filler into the organosilicon system, quaternary ammonium-treated hydroxyapatite exhibits antibacterial effects and forms physical cross-linking points in the matrix, enhancing the material's tear and tensile strength while maintaining sufficient mechanical strength, low hardness, and a pleasant feel. Simultaneously, the hydroxyl groups on the hydroxyapatite surface form hydrogen bonds with the organosilicon molecular chains, improving the surface smoothness and reducing the inherent roughness of silicone rubber. Furthermore, quaternary ammonium-treated hydroxyapatite exhibits good interfacial compatibility with the organosilicon matrix, facilitating uniform dispersion and preventing localized stress concentrations caused by agglomeration.
[0022] Low molecular weight vinyl organopolysiloxanes are used to form the main skeleton of elastomers. Low molecular weight methyl polysiloxane molecular chains do not participate in hydrosilylation crosslinking reactions. They are inserted between polymer molecular chains to increase the interchain spacing, weaken intermolecular forces, dilute the crosslinking network density, improve flexibility and elongation at break, and improve the smooth feel of the surface.
[0023] Low-molecular-weight polyether-modified polyorganosiloxanes are used to improve surface hydrophilicity, enhance skin-friendliness, improve multi-component compatibility, and promote uniform dispersion of inorganic fillers. Furthermore, when low-molecular-weight polyether-modified polyorganosiloxanes are incorporated into silicone rubber, the flexible polyether segments act as internal plasticizers, reducing tensile strength but increasing elongation at break. In some specific embodiments of this invention, the low-molecular-weight polyether-modified polyorganosiloxane is specifically polyether-modified silicone oil, the low-molecular-weight methyl polysiloxane is specifically methyl silicone oil, and the hydrosilylation catalyst is specifically a commercially available PT-5000 hydrosilylation catalyst.
[0024] Hydrosilylation crosslinking agents are used to hydrosilylate vinyl groups during the curing reaction. Hydrosilylation catalysts are used to initiate the curing reaction.
[0025] Specifically, the quaternary ammonium surface-treated hydroxyapatite is obtained by modifying hydroxyapatite with quaternary ammonium alkoxysilane or quaternary ammonium alkoxypolysiloxane.
[0026] Quaternary ammonium alkoxysilanes are molecules that simultaneously contain hydrolyzable alkoxysilane groups (such as —Si(OCH3)3, —Si(OC2H5)3) and quaternary ammonium cationic groups (—N + The organosilicon compound (R3) possesses both coupling ability and antibacterial / antistatic functions. In a specific embodiment of the present invention, one of the following is used for modification: dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride, dimethyloctadecyl[3-(triethoxysilyl)propyl]ammonium chloride, the quaternization product of 3-chloropropyltrimethoxysilane, and benzyldimethylsilylpropylammonium chloride.
[0027] Quaternary ammonium alkoxy polysiloxanes are molecules that simultaneously contain hydrolyzable alkoxysilane groups (such as -Si(OCH3)3, -Si(OC2H5)3) and quaternary ammonium cationic groups (-N). + In specific embodiments of the present invention, organosilicon polysiloxanes (R3) include polysiloxane quaternary ammonium salt-17, polysiloxane quaternary ammonium salt-16, polyether quaternized polysiloxane, DC-5700 polymer, and methoxy-terminated polydimethylsiloxane trimethylammonium chloride, etc.
[0028] After hydrolysis, the alkoxy group (-OR) in the quaternary ammonium alkoxysilane or quaternary ammonium alkoxy polysiloxane molecule undergoes a condensation reaction with the hydroxyl group (-OH) on the surface of hydroxyapatite to form a Si-O-Si covalent bond, which chemically anchors the quaternary ammonium group on the surface of hydroxyapatite, giving hydroxyapatite an antibacterial effect. In addition, it can also improve the dispersibility and interfacial compatibility of hydroxyapatite in organosilicon matrix.
[0029] Specifically, the hydrogen content of the hydrosilylation crosslinking agent is 0.8-1.6%, the Pincus viscosity is 10-30 cs, and the molecular weight dispersion is ≤1.1.
[0030] A hydrogen content of 0.8–1.6% provides ample Si-H reaction sites, enabling thorough hydrosilylation with the vinyl groups of low molecular weight vinyl organopolysiloxanes, ensuring the formation of a complete and reliable three-dimensional crosslinked network in the cured system. A viscosity of 10–30 cSt gives the crosslinking agent excellent flowability and permeability in the system, allowing it to disperse rapidly and uniformly between the low molecular weight vinyl polysiloxane matrix and fillers, ensuring a uniform distribution of crosslinking reaction sites. In some specific embodiments of the present invention, the hydrosilylation crosslinking agent is specifically a hydrogen-terminated dimethyl polysiloxane.
[0031] Specifically, the low molecular weight vinyl organopolysiloxane includes at least two of the following: vinyl-terminated dimethyl polysiloxane, vinyl-terminated methyl vinyl polysiloxane, methyl vinyl dimethyl polysiloxane, phenyl vinyl polysiloxane, dimethyl vinyl-terminated polydimethylsiloxane, and dimethyl vinyl-terminated polydimethyl methyl vinyl siloxane.
[0032] The aforementioned low molecular weight vinyl organopolysiloxane is used to form the main framework of the elastomer. Its vinyl (—CH=CH2) undergoes a hydrosilylation reaction with the Si—H bond of the hydrosilylation crosslinking agent under the action of a platinum catalyst to form a three-dimensional crosslinked network.
[0033] Specifically, the silica in components A and B is fumed silica, and the specific surface area of the silica is 200–240 m². 2 / g; The nano-alumina particles in components A and B have a particle size of 80–150 nm. The TPU microspheres in components A and B have a particle size of 0.8–1.2 μm; The silicone resin in components A and B is MQ silicone resin, and the groups attached to the silicon atoms of the silicone resin are one or more of methyl, phenyl and vinyl groups, and the number average molecular weight of the silicone resin is 4000 to 5000.
[0034] Silica plays a reinforcing role. Fumed silica has very few impurities and a narrow particle size distribution. When uniformly dispersed in a silicone rubber matrix, it exhibits low light scattering, maintaining the high transparency of the vulcanized rubber. Nano-alumina is used to improve the thermal conductivity of the silicone composition and enhance the skin-feel simulation effect. TPU microspheres increase the smoothness and are easily integrated with the system. The silicone resin contains silanol groups in its molecular structure and is used to increase crosslinking. Low-molecular-weight polysiloxanes with low molecular weight dispersion achieve low hardness after crosslinking and curing, ensuring softness.
[0035] The methyl groups in silicone resins enhance basic properties, while vinyl groups can participate in reactions, providing active sites for addition crosslinking. The phenyl groups, on the other hand, improve light transmittance and stability. In some specific embodiments of this invention, the MQ silicone resin is specifically a methylMQ silicone resin.
[0036] The silanol groups (Si-OH) in the silicone resin molecule can undergo condensation reactions with the -OH groups of the terminal hydroxyl polysiloxanes and the alkoxysilane crosslinking agents in the system to form Si-O-Si covalent bonds, constructing a second condensation crosslinking network in addition to the addition crosslinking network. Through the synergistic effect of the dual crosslinking network, the crosslinking points are more uniformly distributed, network defects are reduced, and the organosilicon composition can maintain sufficient mechanical strength even at low hardness, effectively alleviating the contradiction between ultra-softness and strength.
[0037] Specifically, the powder treatment agents in components A and B include one or more of hydroxyl-terminated polydimethylsiloxane, vinyl hydroxyl-terminated polydimethylsiloxane, dimethyldimethoxysilane, dimethyldiethoxysilane, methyltrimethoxysilane, vinyltriethoxysilane, glycidylpropyltrimethoxysilane, and methacrylate-propyltrimethoxysilane.
[0038] The above-mentioned powder treatment agent is evenly dispersed throughout the curing system, which can better control the curing effect.
[0039] Specifically, component A includes a structure control agent and a color paste, and component B includes an inhibitor and a color paste; the structure control agent includes one or more of alkylsilanol, oligomeric hydroxyl-terminated polydimethylsiloxane, hydroxyl-terminated polymethylvinylsiloxane, and trimethylsilanol. The inhibitors include one or more of 3-hydroxybutyne, 3-methyl-1-dodecyn-3-ol, 1-ethynyl-1-cyclohexanol, 2-methyl-3-butynyl-2-ol, 3-methyl-1-ethynyl-3-ol, or 3,5-dimethyl-1-hexynyl-3-ol.
[0040] Structure control agents and inhibitors are used to provide storage stability for component A or component B. The surface of fumed silica contains a large number of silanol groups (Si-OH), which can form hydrogen-bonded chemisorption with oxygen atoms in the polysiloxane molecular chain, causing the organosilicon composition to continuously increase in viscosity and gradually harden and lose fluidity during storage. Structure control agents contain active hydroxyl groups (-OH or Si-OH), which can preferentially undergo condensation reactions with the silanol groups on the fumed silica surface or form stronger hydrogen bonds, thereby competitively occupying the active sites on the fumed silica surface, blocking the hydrogen bonding between fumed silica and the polymer chain, inhibiting structuring, and enabling the organosilicon composition to maintain stable rheological properties and processability during storage.
[0041] Inhibitors can temporarily occupy the active sites of catalysts, effectively inhibiting addition reactions at room temperature and extending the pot life of rubber compounds.
[0042] Pigments are used to give bionic skin a natural skin tone simulation effect.
[0043] Specifically, the hydrosilylation catalyst is a platinum complex catalyst, and the platinum content of the hydrosilylation catalyst is 4500-5500 ppm.
[0044] In a specific embodiment of the present invention, the platinum complex catalyst is a complex of platinum complex and organopolysiloxane, wherein the platinum complex is prepared by platinum and tetramethyldivinyldisiloxane.
[0045] This invention also provides a method for preparing an organosilicon composition for human biomimetic skin, comprising the following steps: Preparation of quaternary ammonium surface-treated hydroxyapatite: Hydroxyapatite was modified to obtain quaternary ammonium surface-treated hydroxyapatite; Preparation of matrix adhesive: Silica, nano-alumina, TPU microspheres and powder treatment agent are kneaded for 1.5 to 2.5 hours to obtain premixed powder; Quaternary ammonium surface-treated hydroxyapatite, low molecular weight vinyl organopolysiloxane, low molecular weight methyl polysiloxane, low molecular weight polyether modified polyorganosiloxane, and silicone resin are added to the premixed powder. After stirring and kneading evenly, the mixture is heated to 110-130℃ and kneaded for 1-2 hours; then heated to 140-150℃ and kneaded for 2.5-3.5 hours; subsequently, it is cooled and stirred for 0.5-1 hour to obtain the matrix adhesive. Preparation of component A: Add hydrosilylation catalyst, component A auxiliary agent and another part of low molecular weight vinyl organopolysiloxane to the matrix gel to obtain component A; Preparation of component B: Add the hydrosilylation crosslinking agent and component B auxiliary agent to the matrix adhesive to obtain component B.
[0046] The total amount of low molecular weight vinyl organopolysiloxane in component A includes the amount in the matrix adhesive and the amount added during the preparation of component A.
[0047] Specifically, the step of preparing quaternary ammonium surface-treated hydroxyapatite includes: adding a quaternary ammonium surface-treatment agent and a surface-treatment catalyst to hydroxyapatite, kneading at 50-70°C for 2-4 hours to obtain quaternized grafted surface-treated modified hydroxyapatite; the quaternary ammonium surface-treatment agent includes quaternary ammonium alkoxysilane or quaternary ammonium alkoxy polysiloxane.
[0048] Example 1 A method for preparing an organosilicon composition for human biomimetic skin includes the following steps: Preparation of quaternary ammonium surface-treated hydroxyapatite: Add 0.01 parts tetramethylammonium hydroxide to 6 parts hydroxyapatite, mix evenly, and then slowly add 0.5 parts dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride. Knead at 60℃ for 3 hours to obtain quaternary ammonium surface-treated hydroxyapatite. Preparation of matrix adhesive: 4 parts of fumed silica, 1 part of nano alumina, 2 parts of TPU microspheres and 1 part of dimethyldimethoxysilane were kneaded for 2 hours to obtain premixed powder; Add 70 parts of vinyl-terminated dimethyl polysiloxane with a viscosity of 2000 CS (25℃) and a vinyl content of 0.2%, 3 parts of vinyl-terminated methyl vinyl polysiloxane with a viscosity of 10000 CS (25℃) and a vinyl content of 0.6%, 2 parts of methyl silicone oil with a viscosity of 10000 CS (25℃), 1 part of polyether-modified silicone oil with a viscosity of 5000 CS (25℃), 1 part of methyl MQ silicone resin with a number average molecular weight of 4500, 0.5 parts of 3-hydroxybutyne, and 0.5 parts of color paste to the premixed powder. The molecular weight dispersion of vinyl-terminated dimethyl polysiloxane, vinyl-terminated methyl vinyl polysiloxane, polyether-modified silicone oil, and methyl silicone oil is ≤1.3. After stirring and kneading evenly, heat to 120℃ and continue kneading for 1.5 h, then heat to 145℃ and knead for 3 h, and then continue low-speed cold stirring for 1 h to obtain the matrix adhesive. Preparation of component A: Add 0.11 parts of PT-5000 to the above matrix adhesive, and then add 2.5 parts of vinyl-terminated methyl vinyl polysiloxane with a viscosity of 2000CS (25℃) and a vinyl content of 2.0% to a disperser and stir to mix evenly. After filtration, component A is obtained. Preparation of component B: 2.2 parts of hydrogen-terminated dimethyl polysiloxane with a hydrogen content of 0.8% and 0.3 parts of 1-ethynyl-1-cyclohexanol were added to the above matrix gel, stirred and mixed in a disperser, and filtered to obtain component B.
[0049] Example 2 A method for preparing an organosilicon composition for human biomimetic skin includes the following steps: Preparation of quaternary ammonium surface-treated hydroxyapatite: Add 0.01 parts tetramethylammonium hydroxide to 10 parts hydroxyapatite and mix evenly. Then slowly add 0.9 parts dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride and knead at 50°C for 2 hours to obtain quaternary ammonium surface-treated hydroxyapatite. Preparation of matrix adhesive: 4 parts of fumed silica, 1 part of nano alumina, 2 parts of TPU microspheres and 1 part of dimethyldimethoxysilane were kneaded for 2 hours to obtain premixed powder; Add 70 parts of vinyl-terminated dimethyl polysiloxane with a viscosity of 2000 CS (25℃) and a vinyl content of 0.2%, 2.5 parts of vinyl-terminated methyl vinyl polysiloxane with a viscosity of 2000 CS (25℃) and a vinyl content of 2.0%, 2 parts of methyl silicone oil with a viscosity of 10000 CS (25℃), 1 part of polyether-modified silicone oil with a viscosity of 5000 CS (25℃), 1 part of methyl MQ silicone resin with a number average molecular weight of 4500, 0.5 parts of 3-hydroxybutyne, and 0.5 parts of color paste to the premixed powder. The molecular weight dispersion of the vinyl-terminated dimethyl polysiloxane, vinyl-terminated methyl vinyl polysiloxane, methyl silicone oil, and polyether-modified silicone oil is ≤1.3. After kneading at 110℃ for 2 hours, the temperature is raised to 140℃ and kneaded for 3.5 hours. Then, the mixture is continued to be cold-stirred at low speed for 1 hour to obtain the matrix gel. Preparation of component A: 0.11 parts of PT-5000, viscosity of 2000CS (25℃), vinyl-terminated methyl vinyl polysiloxane with a vinyl content of 2.0% and 2.5 parts of the above matrix adhesive were added, dispersed and stirred until homogeneous, and then filtered to obtain component A; Preparation of component B: 2.2 parts of hydrogen-terminated dimethyl polysiloxane with a hydrogen content of 0.8% and 0.3 parts of 1-ethynyl-1-cyclohexanol were added to the matrix gel prepared according to the above steps, stirred and mixed in a disperser, and filtered to obtain component B.
[0050] Example 3 A method for preparing an organosilicon composition for human biomimetic skin includes the following steps: Preparation of quaternary ammonium surface-treated hydroxyapatite: Add 0.01 parts tetramethylammonium hydroxide to 6 parts hydroxyapatite, stir evenly, and then slowly add 3 parts methoxy-terminated polydimethylsiloxanetrimethylammonium chloride. Knead at 70°C for 3 hours to obtain quaternary ammonium surface-treated hydroxyapatite. Preparation of matrix adhesive: 4 parts of fumed silica, 1 part of nano alumina, 2 parts of TPU microspheres and 1 part of dimethyldimethoxysilane were kneaded for 2 hours to obtain premixed powder; Add 70 parts of vinyl-terminated dimethyl polysiloxane with a viscosity of 2000 CS (25℃) and a vinyl content of 0.2%, 3 parts of vinyl-terminated methyl vinyl polysiloxane with a viscosity of 2000 CS (25℃) and a vinyl content of 0.6%, 2 parts of methyl silicone oil with a viscosity of 10000 CS (25℃), 1 part of polyether-modified silicone oil with a viscosity of 5000 CS (25℃), 1 part of methyl MQ silicone resin with a number average molecular weight of 4500, 0.5 parts of 3-hydroxybutyne, and 0.5 parts of color paste to the premixed powder. The molecular weight dispersion of the vinyl-terminated dimethyl polysiloxane, vinyl-terminated methyl vinyl polysiloxane, methyl silicone oil, and polyether-modified silicone oil is ≤1.3. After stirring and kneading evenly, heat to 120℃ and continue kneading for 1.5 h, then heat to 150℃ and knead for 3 h, and then continue low-speed cold stirring for 1 h to obtain the matrix adhesive. Preparation of component A: Add 0.11 parts of PT-5000 to the above matrix adhesive, and then add 2.5 parts of vinyl-terminated methyl vinyl polysiloxane with a viscosity of 2000CS (25℃) and a vinyl content of 2.0% to a disperser and stir to mix evenly. After filtration, component A is obtained. Preparation of component B: 2.2 parts of hydrogen-terminated dimethyl polysiloxane with a hydrogen content of 0.8% and 0.3 parts of 1-ethynyl-1-cyclohexanol were added to the above matrix gel, stirred and mixed in a disperser, and filtered to obtain component B.
[0051] Comparative Example 1 10 parts of silica, 1 part of nano alumina, 2 parts of TPU microspheres and 1 part of dimethyldimethoxysilane were kneaded for 2 hours. The treated powder was added to 70 parts of vinyl-terminated dimethyl polysiloxane with a viscosity of 2000 CS (25℃) and a vinyl content of 0.2%, 3 parts of vinyl-terminated methyl vinyl polysiloxane with a viscosity of 2000 CS (25℃) and a vinyl content of 0.6%, 2 parts of methyl silicone oil with a viscosity of 10000 CS (25℃), 1 part of polyether-modified silicone oil with a viscosity of 5000 CS (25℃), 1 part of methyl MQ silicone resin with a number average molecular weight of 4500, 0.5 parts of 3-hydroxybutyne, and 0.5 parts of color paste. After stirring and kneading evenly, the temperature was raised to 120℃ and kneaded for 1.5 h, then raised to 145℃ and kneaded for 3 h, and then continued to be cold-stirred at low speed for 1 h to obtain the matrix adhesive. Add 0.11 parts of PT-5000 to the above matrix adhesive, and then add 2.5 parts of vinyl-terminated methyl vinyl polysiloxane with a viscosity of 2000CS (25℃) and a vinyl content of 2.0% to a disperser and stir to mix. After filtration, component A is obtained. 2.2 parts of hydrogen-terminated dimethyl polysiloxane with a hydrogen content of 0.8% and 0.3 parts of 1-ethynyl-1-cyclohexanol were added to the above matrix gel, stirred and mixed in a disperser, and filtered to obtain component B.
[0052] Comparative Example 2 13 parts of silica and 1 part of dimethyldimethoxysilane were kneaded for 2 hours. The treated silica was added to 70 parts of vinyl-terminated dimethyl polysiloxane with a viscosity of 2000 CS (25℃), a vinyl content of 0.2%, 3 parts of vinyl-terminated methyl vinyl polysiloxane with a viscosity of 2000 CS (25℃) and a vinyl content of 0.6%, 2 parts of methyl silicone oil with a viscosity of 10000 CS (25℃), 1 part of polyether-modified silicone oil with a viscosity of 5000 CS (25℃), 1 part of methyl MQ silicone resin with a number average molecular weight of 4500, 0.5 parts of 3-hydroxybutyne, and 0.5 parts of color paste. After stirring and kneading evenly, the temperature was raised to 120℃ and kneaded for 1.5 h, then raised to 145℃ and kneaded for 3 h, and then continued to be cold-stirred at low speed for 1 h. After cooling, the base adhesive was obtained. Add 0.11 parts of PT-5000 to the above base adhesive, and then add 2.5 parts of vinyl-terminated methyl vinyl polysiloxane with a viscosity of 2000CS (25℃) and a vinyl content of 2.0% to a disperser and stir until homogeneous. After filtration, obtain component A.
[0053] 2.2 parts of hydrogen-terminated dimethyl polysiloxane with a hydrogen content of 0.8% and 0.3 parts of ethynylcyclohexanol were added to the above base gel, stirred and mixed in a disperser, and filtered to obtain component B.
[0054] Comparative Example 3 Under stirring and kneading, add 0.01 parts of tetramethylammonium hydroxide to 10 parts of hydroxyapatite, stir evenly, and then slowly add 0.9 parts of dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride. Knead at 50-70℃ for 3 hours to obtain dimethyloctadecylsilylpropylammonium grafted hydroxyapatite. Eight parts of silica, one part of nano-alumina, two parts of TPU microspheres, and one part of dimethyldimethoxysilane were kneaded for 2 hours.
[0055] The two powders treated above were added to 70 parts of vinyl-terminated dimethyl polysiloxane with a viscosity of 2000 CS (25℃) and a vinyl content of 0.2%, 3 parts of vinyl-terminated methyl vinyl polysiloxane with a viscosity of 2000 CS (25℃) and a vinyl content of 0.6%, 2 parts of methyl silicone oil with a viscosity of 10000 CS (25℃), 1 part of polyether-modified silicone oil with a viscosity of 5000 CS (25℃), 1 part of methyl MQ silicone resin with a number average molecular weight of 4500, 0.5 parts of 3-hydroxybutyne and 0.5 parts of color paste. After stirring and kneading evenly, the temperature was raised to 120℃ and kneaded for 1.5 h, then raised to 145℃ and kneaded for 3 h, and then continued to be cold-stirred at low speed for 1 h to obtain the matrix adhesive. Add 0.11 parts of PT-5000 to the above matrix adhesive, and then add 2.5 parts of vinyl-terminated methyl vinyl polysiloxane with a viscosity of 2000CS (25℃) and a vinyl content of 2.0% to a disperser and stir to mix. After filtration, component A is obtained. 2.2 parts of hydrogen-terminated dimethyl polysiloxane with a hydrogen content of 0.8% and 0.3 parts of 1-ethynyl-1-cyclohexanol were added to the above matrix gel, stirred and mixed in a disperser, and filtered to obtain component B.
[0056] Comparative Example 4 Under stirring and kneading, add 0.01 parts of tetramethylammonium hydroxide to 6 parts of hydroxyapatite, stir evenly, and then slowly add 0.5 parts of dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride. Knead at 50-70℃ for 3 hours to obtain dimethyloctadecylsilylpropylammonium grafted hydroxyapatite. Four parts of silica, one part of nano-alumina, two parts of TPU microspheres and one part of dimethyldimethoxysilane were kneaded for 2 hours. The two powders treated above were added to 70 parts of vinyl-terminated dimethyl polysiloxane with a viscosity of 40000 CS (25℃) and a vinyl content of 0.2%, 3 parts of vinyl-terminated methyl vinyl polysiloxane with a viscosity of 2000 CS (25℃) and a vinyl content of 0.6%, 2 parts of methyl silicone oil with a viscosity of 10000 CS (25℃), 1 part of polyether-modified silicone oil with a viscosity of 5000 CS (25℃), 1 part of methyl MQ silicone resin with a number average molecular weight of 4500, 0.5 parts of 3-hydroxybutyne and 0.5 parts of color paste. After stirring and kneading evenly, the temperature was raised to 120℃ and kneaded for 1.5 h, then raised to 145℃ and kneaded for 3 h, and then continued to be cold-stirred at low speed for 1 h to obtain the matrix adhesive. Add 0.11 parts of PT-5000 to the above matrix adhesive, and then add 2.5 parts of vinyl-terminated methyl vinyl polysiloxane with a viscosity of 40000 CS (25℃) and a vinyl content of 2.0% to a disperser and stir to mix. After filtration, component A is obtained. 2.2 parts of hydrogen-terminated dimethyl polysiloxane with a hydrogen content of 0.8% and 0.3 parts of 1-ethynyl-1-cyclohexanol were added to the above matrix gel, stirred and mixed in a disperser, and filtered to obtain component B.
[0057] Comparative Example 5 Under stirring and kneading, add 0.01 parts of tetramethylammonium hydroxide to 6 parts of hydroxyapatite, stir evenly, and then slowly add 0.5 parts of dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride. Knead at 50-70℃ for 3 hours to obtain dimethyloctadecylsilylpropylammonium grafted hydroxyapatite. Four parts of silica, one part of nano-alumina, two parts of TPU microspheres and one part of dimethyldimethoxysilane were kneaded for 2 hours. The two powders treated above were added to 70 parts of vinyl-terminated dimethyl polysiloxane with a viscosity of 40000 CS (25℃) and a vinyl content of 0.2%, 3 parts of vinyl-terminated methyl vinyl polysiloxane with a viscosity of 2000 CS (25℃) and a vinyl content of 0.6%, 1 part of methyl MQ silicone resin with a number average molecular weight of 4500, 0.5 parts of 3-hydroxybutyne and 0.5 parts of color paste. After stirring and kneading evenly, the temperature was raised to 120℃ and kneaded for 1.5 h, then raised to 145℃ and kneaded for 3 h, and then continued to be cold stirred at low speed for 1 h to obtain the matrix adhesive. Add 0.11 parts of PT-5000 to the above matrix adhesive, and then add 2.5 parts of vinyl-terminated methyl vinyl polysiloxane with a viscosity of 40000 CS (25℃) and a vinyl content of 2.0% to a disperser and stir to mix. After filtration, component A is obtained. 2.2 parts of hydrogen-terminated dimethyl polysiloxane with a hydrogen content of 0.8% and 0.3 parts of 1-ethynyl-1-cyclohexanol were added to the above matrix gel, stirred and mixed in a disperser, and filtered to obtain component B.
[0058] Components A and B obtained from Examples 1-3 and Comparative Examples 1-5 were mixed evenly at a weight ratio of 1:1 and placed in a vacuum desiccator. The vacuum pump was turned on to degas the mixture. The degassed sample was poured into a mold and vulcanized under pressure. Vulcanization conditions: (130±5)℃ for 3 minutes, followed by cooling to room temperature to obtain test samples. The test samples were tested for hardness, tensile strength, elongation at break, compression set, thermal conductivity, resilience, coefficient of dynamic friction, and feel. The results are shown in Table 1. The tests were conducted according to the following standards: GB / T 531.1-2008 Test method for indentation hardness of vulcanized rubber or thermoplastic rubber; GB / T 528-2008 "Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber", using dumbbell type 1 specimens to determine tensile strength and elongation at break. GB / T 529-2008 "Determination of tear strength of vulcanized rubber or thermoplastic rubber (trouser-shaped, right-angled and crescent-shaped specimens)" stipulates that a right-angled specimen without a notch should be used. GB / T 1681-2009 Determination of resilience of vulcanized rubber; ISO 22007-2:2022 "Determination of thermal conductivity and thermal diffusivity of plastics—Transient planar heat source method"; GB / T 10006-2021 Determination of the coefficient of friction of plastic films and sheets; The tactile test involves the same person applying the same force to linearly slide the sample surface to determine the skin feel effect, which is evaluated as smooth or resistant.
[0059] Table 1 - Test Results
[0060] Comparing the test results of Examples 1-3 and Comparative Examples 1-5, it can be seen that Comparative Example 1, without hydroxyapatite, has a worse supporting effect on the system, significantly increased hardness, worse resilience, and larger compression set; Comparative Example 2, with only silica as filler, has increased hardness, decreased thermal conductivity, and worse resilience; Comparative Example 3, with the addition of more powder, has increased hardness and worse resilience; Comparative Example 4, with increased silicone oil viscosity, has increased hardness and worse skin feel; Comparative Example 5, without low-viscosity silicone oil, has increased hardness, worse resilience, and worse skin feel.
[0061] The technical principles of the present invention have been described above with reference to specific embodiments. These descriptions are merely for explaining the principles of the invention and should not be construed as limiting the scope of protection of the invention in any way. Based on this explanation, those skilled in the art can readily conceive of other specific embodiments of the invention without inventive effort, and these equivalent variations or substitutions are all included within the scope defined by the claims of this application.
Claims
1. A silicone composition for use with biomimetic human skin, characterized in that, Includes component A and component B; Component A, by mass fraction, comprises the following components: 1-10 parts quaternary ammonium surface-treated hydroxyapatite, 1-5 parts silica, 1-5 parts nano-alumina, 1-3 parts TPU microspheres, 1-5 parts silicone resin, 1-2 parts powder treatment agent, 10-80 parts low molecular weight vinyl organopolysiloxane, 1-10 parts low molecular weight methyl polysiloxane, 0.1-2 parts low molecular weight polyether modified polyorganosiloxane, 0.01-1 part hydrosilylation catalyst, and 0.01-1 part Component A additive; Component B, by mass fraction, comprises the following components: 1-10 parts quaternary ammonium surface-treated hydroxyapatite, 1-8 parts silica, 1-3 parts nano-alumina, 1-3 parts TPU microspheres, 1-5 parts silicone resin, 1-2 parts powder treatment agent, 10-80 parts low molecular weight vinyl organopolysiloxane, 1-10 parts low molecular weight methyl polysiloxane, 0.1-2 parts low molecular weight polyether modified polyorganosiloxane, 1-8 parts hydrosilylation crosslinking agent, and 0.01-1 parts component B additive; The viscosity of the low molecular weight vinyl organopolysiloxane in components A and B is 1500–2500 CS (25°C), and the molecular weight dispersion is ≤1.3; the viscosity of the low molecular weight methyl polysiloxane in components A and B is 9000–11000 CS (25°C), and the molecular weight dispersion is ≤1.3; the viscosity of the low molecular weight polyether modified polyorganosiloxane in components A and B is 4000–7000 CS (25°C).
2. The organosilicon composition for human biomimetic skin according to claim 1, characterized in that, The quaternary ammonium surface-treated hydroxyapatite is obtained by modifying hydroxyapatite with quaternary ammonium alkoxysilane or quaternary ammonium alkoxypolysiloxane.
3. The organosilicon composition for human biomimetic skin according to claim 1, characterized in that, The hydrosilylation crosslinking agent has a hydrogen content of 0.8-1.6%, a Pint viscosity of 10-30 cs, and a molecular weight dispersion of ≤1.
1.
4. The organosilicon composition for human biomimetic skin according to claim 1, characterized in that, The low molecular weight vinyl organopolysiloxane includes at least two of the following: vinyl-terminated dimethyl polysiloxane, vinyl-terminated methyl vinyl polysiloxane, methyl vinyl dimethyl polysiloxane, phenyl vinyl polysiloxane, dimethyl vinyl-terminated polydimethylsiloxane, and dimethyl vinyl-terminated polydimethyl methyl vinyl siloxane.
5. The organosilicon composition for human biomimetic skin according to claim 1, characterized in that, The silica in components A and B is fumed silica, and the specific surface area of the silica is 200-240 m². 2 / g; The nano-alumina particles in components A and B have a particle size of 80–150 nm. The TPU microspheres in components A and B have a particle size of 0.8–1.2 μm; The silicone resin in components A and B is MQ silicone resin, and the groups attached to the silicon atoms of the silicone resin are one or more of methyl, phenyl and vinyl groups, and the number average molecular weight of the silicone resin is 4000 to 5000.
6. The organosilicon composition for human biomimetic skin according to claim 1, characterized in that, The powder treatment agents in components A and B include one or more of hydroxyl-terminated polydimethylsiloxane, vinyl hydroxyl-terminated polydimethylsiloxane, dimethyldimethoxysilane, dimethyldiethoxysilane, methyltrimethoxysilane, vinyltriethoxysilane, glycidylpropyltrimethoxysilane, and methacrylate-propyltrimethoxysilane.
7. The organosilicon composition for human biomimetic skin according to claim 1, characterized in that, The auxiliary component A includes a structure control agent and a color paste, and the auxiliary component B includes an inhibitor and a color paste; The inhibitors include one or more of 3-hydroxybutyne, 3-methyl-1-dodecyn-3-ol, 1-ethynyl-1-cyclohexanol, 2-methyl-3-butynyl-2-ol, 3-methyl-1-ethynyl-3-ol, or 3,5-dimethyl-1-hexynyl-3-ol.
8. The organosilicon composition for human biomimetic skin according to claim 1, characterized in that, The hydrosilylation catalyst is a platinum complex catalyst with a platinum content of 4500–5500 ppm.
9. A method for preparing an organosilicon composition for human biomimetic skin, characterized in that, The preparation of the organosilicon composition for human biomimetic skin according to any one of claims 1 to 8 comprises the following steps: Preparation of quaternary ammonium surface-treated hydroxyapatite: Hydroxyapatite was modified to obtain quaternary ammonium surface-treated hydroxyapatite; Preparation of matrix adhesive: Silica, nano-alumina, TPU microspheres and powder treatment agent are kneaded for 1.5 to 2.5 hours to obtain premixed powder; Quaternary ammonium surface-treated hydroxyapatite, low molecular weight vinyl organopolysiloxane, low molecular weight methyl polysiloxane, low molecular weight polyether modified polyorganosiloxane, and silicone resin are added to the premixed powder. After stirring and kneading evenly, the mixture is heated to 110-130℃ and kneaded for 1-2 hours; then heated to 140-150℃ and kneaded for 2.5-3.5 hours; subsequently, it is cooled and stirred for 0.5-1 hour to obtain the matrix adhesive. Preparation of component A: Add hydrosilylation catalyst, component A auxiliary agent and another part of low molecular weight vinyl organopolysiloxane to the matrix gel to obtain component A; Preparation of component B: Add the hydrosilylation crosslinking agent and component B auxiliary agent to the matrix adhesive to obtain component B.
10. A method for preparing an organosilicon composition for human biomimetic skin according to claim 9, characterized in that, The steps for preparing quaternary ammonium surface-treated hydroxyapatite include: adding a quaternary ammonium surface-treatment agent and a surface-treatment catalyst to hydroxyapatite, kneading at 50-70°C for 2-4 hours to obtain quaternized grafted surface-treated modified hydroxyapatite; the quaternary ammonium surface-treatment agent includes quaternary ammonium alkoxysilane or quaternary ammonium alkoxypolysiloxane.